Cholecystocolonic Fistulas from Diverticulosis: A Potentially Missable Cause of Liver Abscesses - Ben Warner; Terry Wong; Philip Berry (Case Reports in Gastrointestinal Medicine)
Cholecystocolonic fistulas (CCF) due to colonic diverticulosis are a rare cause of liver abscesses. It is even rarer to simultaneously have choledocholithiasis, another cause for liver abscesses. In this case report, we found both pathologies and emphasise the need to study cholangiograms carefully so as not to miss alternative diagnoses.